A Symphony of Seasons: Linking Climate Fluctuations to Avian Migration Behavior at Okhla Bird Sanctuary, Greater Noida - Gupta, Sheela (Journal for Research in Applied Sciences and Biotechnology, 2023)
The Okhla Bird Sanctuary, nestled in the heart of Greater Noida, stands as a crucial haven for migratory avian species. Against the backdrop of climate change, this study investigates the intricate relationship between climate fluctuations and avian migration behavior within the sanctuary. Through an extensive analysis of climate data and bird monitoring spanning multiple seasons, this research unveils the dynamic symphony of seasons that orchestrates avian movements. It explores the complex web of interactions between climate variables and the timing, routes, and behavior of migratory birds. Our findings illustrate that climate fluctuations have a profound impact on avian migration patterns. Seasonal and interannual variations in climate conditions directly influence the timing and duration of migratory journeys. As the world warms, these fluctuations are becoming increasingly pronounced, posing new challenges to avian populations. This study's insights are of paramount importance for both avian conservation and climate adaptation efforts. By comprehensively understanding how climate change affects the intricate dance of migratory birds in the Okhla Bird Sanctuary, we can better inform conservation strategies and habitat management. In a world where the rhythm of nature is increasingly influenced by human-induced climatic shifts, deciphering this symphony of seasons not only enhances our understanding of the natural world but also empowers us to protect the delicate balance that sustains these feathered voyagers.